Cooperation of the EU and Kazakhstan on civil society development in Kazakhstan (International relations and international law Journal, 2018)
Development of civil society is considered to be one of the crucial pillars of post-Communist democratization. The European Union (EU) devotes remarkable attention and effort to civil society development. This study aims to shed light on the cooperation of the EU and Kazakhstan on civil society development in Kazakhstan. To this end, first the methodology of the study is clarified. Second, the historical background of civil society development in Kazakhstan is addressed. Third, the phases of post-Soviet civil society development are explored. Fourth, EU’s cooperation with the government and civil society actors is analyzed. As a conclusion, the study discusses that although the cooperation between Kazakhstan and the EU in the area of civil society development in Kazakhstan is marred with difficulties and failed to bring about significant advance so far, cooperation needs to be sustained. Kazakhstan is willing to willing to carry out reform within the contours of its national interest and stability. Astana prioritizes state building and stability over democratization. Kazakhstan is also careful about keeping delicate balances in its multi-vector foreign policy. The EU has acted in line with the preference s of Kazakhstan so far by implementing a developmental approach rather than a political one. The developmental approach of the EU is expected to deliver the desired results slowly. The post-Soviet generation of Kazakhstan is much more devoted to change compared to the generation in administration now. The change will gain momentum when the new generation fills important positions in the important positions in administration.Key words: Kazakhstan, the European Union, Civil Society, Democratization, Stability.